Competitive effects of cable networks on FTTx deployment - Fabian Queder (International Telecommunications Society (ITS), 2019)
The European Union and its Member States have set themselves ambitious broadband targets. By 2025 the EU aims to provide access to at least 100 Mpbs to all European citizens and gigabit connectivity for all main socio-economic drivers such as schools and hospitals (European Commission 2016). Germany even aims for nationwide gigabit-coverage by 2025 (Die Bundesregierung 2017). In the light of massive investments in NGA deployment that are necessary to reach these targets, it is intensively discussed which economic and market conditions foster telecommunications operators' investments in FTTP-infrastructures. With the introduction of DOCSIS, which enabled cable networks to deliver broadband services, European policy makers considered cable networks a potential source for competition in fixed telecommunication markets. In the early 2000s, due to regulatory pressure, European incumbents divested their cable business and sold it to private companies enabling a substantial part of European households to choose between a cable network operator and the incumbent for broadband and telephony provisioning. Today's European telecommunications markets are therefore characterized by inter-platform competition between cable network operators, incumbents, and alternative operators that rolled-out their own infrastructure. In this regard, there is a vibrant debate (yet, barely covered by empirical studies) which effect the presence of cable networks have on the incumbent's as well as on alternative operators' investments in FTTx. On one hand, it is argued that higher cable coverage could increase investments as incumbents and alternative operators upgrade their networks in order to avoid losing market shares to competing cable networks. On the other hand, it is argued that the existence of cable networks hampers investments in FTTx-networks since operators investing in areas with existing coax-cable networks execute these investments against an existing infrastructure and an existing customer base. This penetration risk due to a lower (anticipated and actual) take-up, effectively reduces revenues and the ability to recover investment costs and consequently to invest without governmental subsidies...
Keywords: 330